Development of AAV-mediated gene therapy for autosomal recessive bestrophinopathy - Wood, S (2017)
The bestrophinopathies are a set of inherited retinal degenerations caused by mutations in BEST1, and include Best vitelliform macular dystrophy (BVMD), autosomal dominant vitreoretinochoroidopathy (ADVIRC) and autosomal recessive bestrophinopathy (ARB). The corresponding protein, bestrophin-1, is localised to the basolateral membrane of the retinal pigment epithelium (RPE), where it is thought to function as a Ca2+-activated Cl- channel. Currently, there are no treatments for these conditions. In recent years, gene therapy has emerged as an exciting treatment option for inherited retinal disorders (IRDs). Gene delivery to retinal cells using a recombinant adeno-associated virus (rAAV) has produced positive results in several IRDs. Given the recessive nature of ARB, this thesis proposes that the rAAV-mediated delivery of bestrophin-1 to the RPE could represent a potential therapy. The aims of this thesis were to produce and compare rAAV vectors in vitro and in vivo for protein expression, localisation following transduction, restoration of chloride conductance in vitro and safety following sub-retinal injection in vivo. Following the production of two rAAV vectors expressing bestrophin-1, western blots confirmed bestrophin-1 protein expression following transduction of HEK293 cells in vitro. Immunocytochemistry (ICC) revealed bestrophin-1 expression that was localised to the cytosol. Whole-cell patch-clamping revealed a significant increase in chloride conductance in HEK293 cells transduced with AAV-BEST1 vectors which was then ablated upon the removal of chloride from the buffers. Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) indicated that the bestrophin-1 protein was successfully transcribed and translated from the BEST1 coding sequence (CDS). Sub-retinal injections of AAV-BEST1 produced bestrophin-1 expression in the RPE of wild-type C57BL/6 mice however significant retinal thinning was seen at higher doses of vector. In conclusion, rAAV-mediated transfer of bestrophin-1 to the RPE has potential to be a future therapy for ARB, however safety issues need to be addressed and an RPE-specific promoter could be more suitable.